Asian Corporate Recovery : Findings from Firm-Level Surveys in Five Countries - Dwor-Frecaut, Dominique; Colapco, Francis X.; Hallward-Driemeier, Mary; World Bank Staff (Washington : World Bank Publications, 2000)
Annotation.
Includes reference
Keywords: Financial crises -- Congresses -- Southeast Asia; Industrial management -- Congresses -- Southeast Asia